Influence of different acid etching times on the shear bond strength of brackets bonded to bovine enamel - Clyvis Maurício Ferreira da Silva; André Felipe de Menezes Costa; Ana Rosa Costa; José Guilherme Neves; Ana Paula Terrosi de Godói; Vívian Fernandes Furletti de Góes (Elsevier, 2021)
Introduction: The most used product for surface acid conditioning for enamel is 37-40% phosphoric acid, which promotes greater mechanical retention. Aim: The objective of this study was to compare the shear bond strength (SBS) of brackets bonded to bovine enamel with different acid conditioning protocols and to analyze the surface morphology. Materials and methods: 169 teeth (n = 13) were divided into 4 groups: control group without conditioning (G1), Dental Gel 37% phosphoric acid (Dentsply) (G2), Ultra Etch 35% (Ultradent) (G3) and Attaque gel 37% (Biodinâmica) (G4). Groups G2, G3 and G4 were subdivided according to the conditioning time into: 10 s (a), 15 s (b), 30 s (c) and 60 s (d). The superficial enamel morphology (n = 3) was analyzed using a scanning electron microscopy (SEM) to analyze the depth of the microporosities. The samples were submitted to the shear test (SBS) with the aid of a universal testing machine (INSTRON) with a speed of 1 mm/min. The enamel after debonding was analyzed to determine the adhesive remnant index (ARI) in a stereoscopic magnifying glass. Statistical analysis used: The SBS data were analyzed using two-way ANOVA. ARI data were analyzed using generalized linear models and SEM measurements were analyzed using Kruskal Wallis and Dunn tests. The 95% significance level was used. Results: The SBS within G2, G3 and G4 ranged from 11.11 to 12.66 MPa. ARI score 3 was observed in 35% of the samples. The samples analyzed in the SEM showed microporosity depth rangingfrom 1.28 to 2.48 μm. Conclusions: There was no difference between the acids and times evaluated for SBS. The ARI analysis showed that the studied acids provide protection to the enamel surface, keeping the adhesive attached to the buccal surface after debonding. The increase in conditioning time is directly proportional to the deterioration of the prismatic and interprismatic content.